PENGEMBANGAN MEDIA PEMBELAJARAN DIGITAL BERBASIS POP-UP BOOK PADA MATA PELAJARAN BAHASA INDONESIA DI SDIT MUHAMMADIYAH 6 LHOKSEUMAWE - Putra Sitorus Pane (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to develop a digital Pop-up Book learning media that is valid, practical, and effective in improving the early reading skills of second-grade students at SDIT Muhammadiyah 6 Lhokseumawe. The study was motivated by students' low early reading abilities and the limited use of innovative and interactive learning media in Indonesian language instruction. This research employed the Research and Development (R&D) method using the ADDIE development model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The research subjects included media experts, material experts, and 22 second-grade students of SDIT Muhammadiyah 6 Lhokseumawe. Data were collected through expert validation questionnaires, student response questionnaires, and learning achievement tests in the form of pretests and posttests. The collected data were analyzed using descriptive quantitative analysis to determine the validity, practicality, and effectiveness of the developed media. The findings revealed that the digital Pop-up Book obtained a very feasible category based on evaluations from both media and material experts. Students also gave highly positive responses, indicating that the learning media was attractive, easy to use, and capable of increasing learning motivation. Furthermore, the comparison of pretest and posttest scores demonstrated a significant improvement in students' early reading abilities after using the developed media. Therefore, the digital Pop-up Book learning media is considered valid, practical, and effective for supporting Indonesian language learning, particularly in early reading instruction at the elementary school level.